Atherosclerotic cardiovascular disease risk assessment and predictors of statin use in Filipino‐American Women. (8th April 2019) - Borja‐Hart, Nancy; Graff, J. Carolyn; Nolan, Vikki G.; Wang, Jiajing; Cooper‐DeHoff, Rhonda M.; Ancheta, Irma B.
Summary: What is known and objective: Race and gender disparities in the context of appropriate treatment with lipid‐lowering therapies do exist. The 2013 American College of Cardiology (ACC)/American Heart Association (AHA) guidelines outlined four groups, three for primary prevention and one for secondary prevention, whom would benefit from statin therapy to target atherosclerotic cardiovascular disease (ASCVD). The application of these recommendations in Filipino women living in the United States is unknown; however, this population is known to have elevated cardiovascular risk. Socio‐economic and clinical characteristics that predict statin utilization of this Asian American subgroup need to be explored. Methods: This was an exploratory analysis of data collected during a cross‐sectional study of Filipino‐American Women (FAW). The Pooled Cohort equation was used to estimate 10‐year ASCVD risk. Bivariate analysis was employed to determine the association between statin treatment and clinical and socio‐economic factors. Data were analysed using SAS ® 9.4; statistical significance was set at P  < 0.05. Results and discussion: A total of 384 women (mean age 56.3 years) were included in the original study, and the average 10‐year ASCVD risk was 3.5 ± 3.7%. Upon applying the 2013 ACC/AHA guidelines, 97 FAW were categorized into one of the primary prevention groups. Women considered to benefit from a statin based on the guideline criteria but were not prescribed a statin were considered the not statin treated group (n = 55). From the original cohort, 93 FAW reported current statin therapy use and were categorized as statin treated . The clinical characteristics associated with not being statin treated were as follows: untreated blood pressure ( P  = 0.012), higher diastolic blood pressure ( P  = 0.015), higher total cholesterol ( P  < 0.001), higher triglycerides ( P  = 0.041), higher low‐density lipoprotein ( P  < 0.001) and higher glucose ( P  = 0.011). The socio‐economic factor associated with not being statin treated was having two or more insurance payers ( P  = 0.005). Overall, this population had a waist circumference and body mass index (BMI) that exceeds guidelines for Asian women (31.5 or 80 cm). What is new and conclusion: Predictors of statin utilization in FAW are not well documented in the literature. These findings emphasize room for improvement for the prescribing of statins in primary prevention for this study population. Applying culturally appropriate screening strategies to identify cardiovascular risk factors early such as BMI or waist circumference may assist with quantifying patients into one of the statin benefit groups if eligible. Abstract : Predictors of statin utilization in Filipino‐American Women (FAW) are not well documented in the literature. Overall, the FAW population in this study had a waist circumference and body mass index (BMI) that exceeds guidelines for Asians (<31.5"/80 cm and <23kg/m 2 ). Applying culturally appropriate screening strategies to identify cardiovascular risk factors early such as BMI or waist circumference may assist with quantifying patients into one of the statin benefit groups if eligible.